Effectiveness of Gout Therapy with Polyherbal Extract of Shallot (Allium ascalonicum L.) and Red Ginger (Zingiber officinale var rubrum) in Hyperuricemia Mice - Fathur Rohman Haryadi; Dela Ria Nesti; Ida Tjahajati; Okti Herawati (Jurnal Sain Veteriner, 2020)
Gout can cause inflammation of acute gout arthtritis, as well as other complications. Provision of chemical drugs in the long term have side effects. Shallots (Allium ascalonicum L.) contain flavonoids which can inhibit the xanthine oxidase enzyme, so as to reduce uric acid levels. Red ginger extract (Zingiber officinale var rubrum) is rich in gingerol to reduce uric acid with anti-inflammatory effect. Polyberbal combination is expected to increase the effectiveness of therapy. The research aims to determine the effectiveness of polyherbal combinations. 25 male rats (2-3 months) were divided into five groups, namely negative control, positive control, (P1) 25% red ginger extract: 75% shallot, (P2) 50% red ginger extract: 50% shallot, ( P3) 75% red ginger extract: 25% shallot. Induction of potassium oxonate 250 mg / kg BW intraperitoneally on the 7th day. The first measurement of uric acid on the 14th day with Urid Acid Toos, the 15th to 28th days was administered herbal / chemical drugs according to the group. Measurement of second and third uric acid on days 21 and 28. Data were analyzed by one-way Anova (RAL), further significance tests using Least Significant Different (LSD). The results showed that administration of potassium oxonate and combination of herbal extracts had a significant effect (p <0.05) on uric acid levels in all groups. The most effective herbal combination doses are (P3) 75% red ginger (450 mg / 200 gr) and 25% shallot (150 mg / 200 gr BW). The conclusion of this study is the combination of red ginger extract and shallot can be recommended as a uric acid-lowering agent.